2020
DOI: 10.1186/s13048-020-0609-y
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and lipidomic analysis of exosomes derived from ovarian cancer cells and ovarian surface epithelial cells

Abstract: Background: The limitation of current biomarker of early stage ovarian cancer and the anatomical location of ovarian (depths of the pelvic) make ovarian cancer difficult to be detected in early stage. Growing evidence shows exosomes as key information transmitters, it carried molecules, such as miRNAs, proteins, lipids, double-stranded DNA have been reported as promising biomarkers in many diseases. However, little is known about the protein and lipid composition of ovarian cancer. Methods: Here, we report pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 47 publications
1
64
0
Order By: Relevance
“…These factors are either related to tumor development or metastasis. Noticeably, a very recent study showed the higher concentration of lipoprotein lipase (LPL) and collagen type V alpha 2 chain (COL5A2) in exosomes derived from ovarian cancer cells (SKOV-3) compared to ovarian surface epithelial cells (HOSEPiC) by proteomic and lipidomic analysis [ 171 ]. Furthermore, exosomal proteins might be involved in drug resistance.…”
Section: Exosomes In the Pathophysiology Of Female Reproductionmentioning
confidence: 99%
“…These factors are either related to tumor development or metastasis. Noticeably, a very recent study showed the higher concentration of lipoprotein lipase (LPL) and collagen type V alpha 2 chain (COL5A2) in exosomes derived from ovarian cancer cells (SKOV-3) compared to ovarian surface epithelial cells (HOSEPiC) by proteomic and lipidomic analysis [ 171 ]. Furthermore, exosomal proteins might be involved in drug resistance.…”
Section: Exosomes In the Pathophysiology Of Female Reproductionmentioning
confidence: 99%
“…The lipid composition of EVs can be studied in detail using mass spectrometry, high-performance liquid chromatography, nuclear magnetic resonance, gas chromatography-mass spectrometry, and computational approaches [ 56 62 ]. One study identified differences in lipid composition between EVs of ovarian cancer cells and ovarian epithelial cells, and these differences may facilitate early diagnosis [ 63 ]. Another study found that analysis of exosomal lipids was able to distinguish non-small-cell lung cancer in the early or late stages [ 64 ].…”
Section: Biogenesis and Contents Of Evsmentioning
confidence: 99%
“…They identified 1433 proteins and 1227 lipids in the exosomes derived from the two cell lines and observed significant differences in several lipids and proteins in the two exosomes populations. Their study implied combination of proteomic and lipidomic profiles could be a promising approach in the early diagnosis of ovarian cancer ( 49 ). Application of such unique approaches make exosomes excellent candidates for developing biomarkers and strategies for liquid biopsies.…”
Section: Content Of Evs For Immunomodulation and As Candidates Of Liqmentioning
confidence: 99%